Ketidakhadiran Calon Pengantin dalam Praktik Rapak Nikah Perspektif Teori Kepastian Hukum - Karim, Nusaiba Nisa’ul; Arfan, Abbas; Huda, Miftahul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to examine the absence of the bride-to-be in the practice of marriage ceremony on the marriage administrative process and analyze its impact through the application of Gustav Radbruch's Theory of Legal Certainty. This research is a type of empirical juridical research using a qualitative descriptive approach. The research was conducted at KUA, Ringinrejo District, Kediri Regency with the object of research being the Head of KUA as an informant who can provide information about the absence of the bride-to-be in the practice of marriage rapak. In this study, the researcher used primary and secondary data sources. The data collection methods used are interviews and documentation. The data analysis methods used are data processing, data classification, data analysis, and conclusion. The main findings of this study show that in KUA Ringinrejo District there is flexibility when the prospective husband is unable to attend the practice of marriage cards such as through representatives or confirmation via telephone. Although administratively this allows the continuation of the marriage process, from the perspective of Gustav Radbruch's theory of Legal Certainty, which includes justice, utility, and legal certainty, it is found that the absence of the bride-to-be has the potential to cause legal vulnerability, especially related to the legitimacy and administration of the marriage. This research contributes to the discourse on marriage administration reform and the urgency of establishing more adaptive regulations in ensuring legal certainty in the midst of social dynamics of society.